Teacher Conflict in Islamic Elementary Schools: Sources, Types, and Management Strategies Across Urban and Suburban Contexts - Arismunandar Arismunandar; Nurhikmah H; Hengki Wijaya (Jurnal Pendidikan Islam, 2026)
Teacher conflict is a significant organizational issue in schools because it can influence teacher well-being, professional collaboration, and institutional effectiveness; however, limited research has simultaneously examined sources of conflict, types of conflict, and conflict management strategies in Islamic elementary schools across regional contexts. This study aimed to investigate the sources and types of conflict and to analyze the strategies used by teachers to manage conflict in suburban and urban Islamic elementary schools. A convergent mixed-methods design was employed involving 124 teachers in Makassar, Indonesia, consisting of 70 teachers from suburban schools and 54 teachers from urban schools. Quantitative data were analyzed using descriptive statistics and independent-samples t-tests, while qualitative data were collected through Focus Group Discussions to explore teachers’ experiences and perceptions of conflict. The quantitative findings revealed no statistically significant difference between suburban and urban teachers in overall sources of conflict (t = -0.57, p = .570), indicating comparable levels of perceived organizational tension. Significant differences were found in process conflict (t = -2.04, p = .044) and conflict management strategies (t = -21.51, p < .001), with urban teachers reporting stronger use of structured conflict management practices. Qualitative findings showed that suburban conflict was primarily associated with limited resources, workload pressures, and overlapping responsibilities, whereas urban conflict was more closely related to miscommunication, interpersonal tensions, and unclear work procedures. This study contributes an integrative framework for understanding how conflict emerges, manifests, and is managed within Islamic school organizations.